Students' Perceptions of Self-Assessment in Writing Competency - Ketut Novita Sari; Dewi, Ni Luh Putu Eka Sulistia; Wahyuni, Luh Gede Eka (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Students have unique perspectives based on their previous self-assessment experiences. To provide strong evidence that self-assessment can be used successfully and can improve students' writing proficiency, we need to understand how students feel when implementing self-assessment. This study aims to analyze high school students' perceptions regarding the utilization of self-assessment for evaluating writing competency. This study employing a mixed-method approach, the research utilizes a sequential explanatory design involving both quantitative and qualitative methodologies. This study incorporates a questionnaire completed by ninety students and subsequent interviews with five students experienced in self-assessment. Drawing from Van Der Kleij's theory, the questionnaire and interview guide were developed, focusing on two dimensions: the usage and quality of self-assessment. Following completion, 118 students and three experts assessed the questionnaire's validity. The findings indicate that while 50% of students perceive self-assessment as beneficial, both questionnaire analysis and interview data suggest an overall positive perspective among students. Self-reflection through self-assessment enables students to identify strengths and weaknesses, fostering confidence and independence in their revision process. Moreover, it aids educators in monitoring student development and assessing teaching effectiveness. Despite its benefits, students encounter difficulties in applying self-assessment, including uncertainty regarding its purpose and implementation accuracy, leading to a lack of confidence in its application. Addressing these challenges is crucial for optimizing the effectiveness of self-assessment practices in enhancing students' writing competency.